Assessing research activity and capacity of community-based organizations: development and pilot testing of an instrument. - Humphries, Debbie L; Carroll-Scott, Amy; Mitchell, Leif; Tian, Terry; Choudhury, Shonali; Fiellin, David A (Progress in community health partnerships : research, education, and action, 2014)
Although awareness of the importance of the research capacity of community-based organizations (CBOs) is growing, a uniform framework of the research capacity domains within CBOs has not yet been developed.
Keywords: Capacity Building; Community-Based Participatory Research; Cooperative Behavior; Data Collection; Financing, Organized; Humans; Information Dissemination; Program Development; Program Evaluation